(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
An admixture, according to the ASTM C 125-97 standards, is a material other than water, aggregates or hydraulic cement that is used as an ingredient of concrete or mortar, and is added to the batch immediately before or during mixing to enhance the workability. Superplasticizer (SP) is important to enhance the durability as well. Generally, there are four main categories of Superplasticizers- Sulfonated melamine formaldehyde condensates, Sulfonated naphthalene formal dehyde condensates, Modified lignosulfonates and Sulfonic- acid esters and carbohydrate esters. In this study, three different chemically composed superplasticizers were used for a single grade of M 30 concrete to improve the properties of fresh and hardened concrete in severe weather as workability, compressive strength by adopting superplasticizers at desired dosage, compaction factor, and water absorption. Split Tensile Strength, Cube Compressive Strength Test, Flexural Strength test and Slump Cone test were some of the tests carried on fresh and hardened concrete. The three admixtures had quite distinct and different effects, but they all induced a compaction factor of more than 0.84 and the workability increased for all three admixtures when used at a constant water-cement ratio.